Adsorption of Carbon Monoxide (CO) in a Room by Coconut Shell and Durian Skin Activated Carbons - Nurullita, Ulfa; Mifbakhuddin, Mifbakhuddin (Jurnal Kesehatan Masyarakat, 2016)
Cigarettes contain more than 4.000 elements, at least 200 of them are harmful to health. The main toxins are tar, nicotine, and carbon monoxide (CO). The purpose study was to know ability of coconut shell and durian skin activated carbon as adsorbent of CO. The study was pre-experimental with randomized control group only design. Independent variables are types of activated carbon, the dependent variable is concentration of CO. The results showed the lowest in durian skin activated carbon that 29 ppm. The average CO decreased on coconut shell is 68,7 ppm, durian skin is 77,478 ppm. One way anova test to see the difference CO in various of activated carbon p value 0,0001, independent t test to see the difference CO reduction between 2 types activated carbon with p value is 0,0001. Conclusion: there is a differences adsorbtion of CO between coconut shell and durian skin activated carbon.